2021
DOI: 10.2147/tcrm.s296680
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Lifestyle Factors Related to Gastroesophageal Reflux Disease: A Systematic Review

Abstract: We performed this review to clarify which dietary and lifestyle factors are related to gastroesophageal reflux disease. Through a systematic search of the PubMed, EMBASE, China National Knowledge Infrastructure (CNKI), and Chinese BioMedical Literature (CBM) databases, we identified articles with clear definitions of GERD, including nonerosive gastroesophageal reflux disease (NERD), reflux esophagitis (RE) and Barrett’s esophagus (BE), that included dietary and lifestyle factors as independent factors affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 86 publications
3
56
0
8
Order By: Relevance
“…It is of interest that these effects were recorded independently of BMI. Dietary habits such as irregular food consumption, especially in the evening hours, and a diet rich in reflux-promoting factors may also worsen GERD symptoms in obese subjects [ 122 , 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: The Role Of Obesity In Be and Eac Developmentmentioning
confidence: 99%
“…It is of interest that these effects were recorded independently of BMI. Dietary habits such as irregular food consumption, especially in the evening hours, and a diet rich in reflux-promoting factors may also worsen GERD symptoms in obese subjects [ 122 , 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: The Role Of Obesity In Be and Eac Developmentmentioning
confidence: 99%
“…Spicy food, eating citrus fruits with meals, fried foods, greasy foods, eating snacks at night, frequently skipping breakfast, eating quickly, eating hot food, and overeating are all positively correlated with GERD. In contrast, vegetarian diets, fruits, vegetables, vitamins, fiber, and proper physical exercise were negatively correlated with GERD [ 26 ]. Among the participants in our study, fatty, fried, and spicy foods were the major dietary factors that aggravated the symptoms of GERD: 49.4% reported symptom aggravation by consuming fatty and fried food, 46.7% by consuming spicy food, and 27.3% by eating tomato products such as tomato sauce and ketchup.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that alcohol consumption is a risk factor for GERD [ 2 , 17 , 26 ]. In our study, we could not evaluate this aspect as alcohol consumption is prohibited in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…42 The strongest risk was associated with "less than 3-hour interval between dinner and bed" (OR 7.45, 95% CI 16.4) and "high-fat diet" (OR 7.568, 95% CI 4.557-8.908), whereas vegetarian diet had the strongest negative relationship (OR 0.34, 95% CI 0.211-0.545). 42 Also, a recent study found that a simple strategy helping GORD patients identify and eliminate dietary triggers significantly reduced symptoms and the need for pharmacological treatment. 43 Lifestyle advice is relevant for all patients, even those on antisecretory therapy.…”
Section: Lifestyle Advicementioning
confidence: 97%
“…Nonetheless, simple dietary and lifestyle advice may suffice for patients with reflux‐like symptoms. A recent meta‐analysis found a clear relationship between reflux‐like symptoms and irregular eating habits, including late‐night snacking, skipping breakfast, eating quickly or eating beyond fullness 42 . The strongest risk was associated with “less than 3‐hour interval between dinner and bed” (OR 7.45, 95% CI 3.38–16.4) and “high‐fat diet” (OR 7.568, 95% CI 4.557–8.908), whereas vegetarian diet had the strongest negative relationship (OR 0.34, 95% CI 0.211–0.545) 42 .…”
Section: Personalised Managementmentioning
confidence: 99%